Strong Lithium Polysulfide Chemisorption on Electroactive Sites of Nitrogen‐Doped Carbon Composites For High‐Performance Lithium–Sulfur Battery Cathodes1. (6th February 2015) - Song, Jiangxuan; Gordin, Mikhail L.; Xu, Terrence; Chen, Shuru; Yu, Zhaoxin; Sohn, Hiesang; Lu, Jun; Ren, Yang; Duan, Yuhua; Wang, Donghai
Abstract: Despite the high theoretical capacity of lithium–sulfur batteries, their practical applications are severely hindered by a fast capacity decay, stemming from the dissolution and diffusion of lithium polysulfides in the electrolyte. A novel functional carbon composite (carbon‐nanotube‐interpenetrated mesoporous nitrogen‐doped carbon spheres, MNCS/CNT), which can strongly adsorb lithium polysulfides, is now reported to act as a sulfur host. The nitrogen functional groups of this composite enable the effective trapping of lithium polysulfides on electroactive sites within the cathode, leading to a much improved electrochemical performance (1200 mAh g −1 after 200 cycles). The enhancement in adsorption can be attributed to the chemical bonding of lithium ions by nitrogen functional groups in the MNCS/CNT framework. Furthermore, the micrometer‐sized spherical structure of the material yields a high areal capacity (ca. 6 mAh cm −2 ) with a high sulfur loading of approximately 5 mg cm −2, which is ideal for practical applications of the lithium–sulfur batteries.